Analysis of nutraceutical properties of four peach cultivars grown in San Pedro and evaluation of the resultant dried slices - Salvañal, Lara; Gabilondo, Julieta; Budde, Claudio Olaf; Corbino, Graciela Beatriz; Lara, Maria Valeria (Ministro de Ciencia y Tecnología, Gobierno de la Provincia de Córdoba, 2022)
Poster